Physicochemical Analysis of Strawberries Coated with Potato Peel Starch Edible Coating with Sungkai Extract - Ardiani, Ajeng Putri; Refilda; Yefrida (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Strawberries are a fruit widely consumed globally, but they have a short shelf life. Consequently, maintaining and storing strawberries is quite challenging. Fruit preservation using edible coatings has gained significant attention due to their cost-effectiveness and ease of preparation. In this study, we compared an edible coating made from potato peel starch to pure starch (Merck), using a mix that included 4% starch, 50% extract from sungkai leaves, and 34% glycerol based on the total starch. An edible coating formulation was applied to strawberries, and physicochemical analysis was carried out on days 0, 2, 4, and 6. The results showed that strawberries coated with edible coating showed more optimal results than strawberries without edible coating on day 4. Strawberries with an edible coating of potato peel starch with the addition of extract from sungkai leaves had the best results: a weight loss of 82.15%, total soluble solids of 9.67 brix, total titratable acid of 1.18%, total antioxidants of 149.3 mg AAE/gFW, and total phenolics of 206,56 mg AAE/Gfw. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action